GABA-ERGIC Deficit in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Neuroradiologists from the Johns Hopkins University School of Medicine investigated the GABAergic component of ADHD using magnetic resonance spectroscopy to measure GABA concentration in somatosensory and motor cortices.